2009
DOI: 10.1111/j.1540-8159.2009.02437.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Performance and Automatic Capture Characteristics of a 3.5‐mm2 Passive Fixation Lead during 1‐Year Follow‐Up

Abstract: The bipolar ventricular pacing lead IsoFlex S 1636/1646T shows a good electrical performance and is mostly compatible with the AutoCapture algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Electrical performances were within ranges retrieved in the literature for the atrium: PCT was comparable to values observed by Kistler et al [9], P-wave amplitude were close to those reported by Rickard [6] and Cornacchia [10], and impedance values compared to those found by Kistler [9] and Lotze et al [11]. In the ventricle, PCT values compared with those reported by Rickard [6] and Lotze et al [11]; sensing amplitude were aligned with Nagatomo et al [12] and Schuchert et al [13]. Finally, impedances were close to those reported by Schuchert [13].…”
Section: Discussionsupporting
confidence: 88%
“…Electrical performances were within ranges retrieved in the literature for the atrium: PCT was comparable to values observed by Kistler et al [9], P-wave amplitude were close to those reported by Rickard [6] and Cornacchia [10], and impedance values compared to those found by Kistler [9] and Lotze et al [11]. In the ventricle, PCT values compared with those reported by Rickard [6] and Lotze et al [11]; sensing amplitude were aligned with Nagatomo et al [12] and Schuchert et al [13]. Finally, impedances were close to those reported by Schuchert [13].…”
Section: Discussionsupporting
confidence: 88%
“…At present, TVI is the only hemodynamic sensor proposed as a tool for ejection surveillance at every beat. While capture recognition based on evoked potential detection still requires the use of low polarization electrodes for full reliability [ 24 26 ], TVI can be recorded with any pacing lead. The TVI system demonstrated excellent sensitivity to capture failure during threshold analysis, coupled with an acceptable specificity.…”
Section: Discussionmentioning
confidence: 99%